Reconnecting School and Society: Defending the School as a Public Institution - Biesta, Gert (Philosophical Inquiry in Education, 2026)
In this essay I reflect on the relationship between ‘school’ and ‘society.’ I do this from the angle of the idea of education as a public good, that is a ‘good’ that should serve ‘the public’ at large, and not just the private interests of some groups or individuals. While there are many countries in which the basic idea of education as a public good is accepted, there is a risk that the ‘right to education’ is exclusively understood in functional terms, where the school has to ‘give’ what society ‘asks’ of it. While this is a legitimate way in which the relationship between school and society can be understood and enacted, it is not the only way. In addition to the idea of the school as a function of and for society, I make a case that the school should also be understood as an institution, and that the task of institutions is to care and protect rather than to perform. It is only if there is a meaningful balance between the school as function and the school as institution, so I will argue, that the school can really be—and remain—a public good. I exemplify what this means by exploring the educational significance of the curriculum.